An overview of African traditional cassava processing and utilization - Hahn, S. (1989)
Cassava is grown in 31 African countries and consumption per capita averages just over 100 kg/year. This article reviews traditional cassava processing and utilization as now practised by small-scale farmers and processors in Africa, and examines the opportunities for improving post-harvest operations in the African continent.